THE APPLICATION OF DIGITAL TECHNOLOGY IN THE PROTECTION AND INHERITANCE OF INTANGIBLE CULTURAL HERITAGE (Proceeding of the International Conference on Arts and Humanities, 2024)
This study addresses the urgent need to preserve and transmit Intangible Cultural Heritage (ICH) in the face of global cultural homogenization and rapid modernization. The primary aim is to explore how digital technologies can be effectively utilized to safeguard and inherit ICH, ensuring that these cultural practices continue to thrive. The research employs a multi-faceted approach, including case studies, technological assessments, and expert interviews to analyze the application of digital technologies in preserving ICH. Specifically, the study investigates the use of digital tools such as 3D scanning, virtual reality (VR), and multimedia archives in documenting, storing, and disseminating cultural artifacts. By examining both successful and challenging implementations, the study provides a comprehensive overview of how these technologies can be applied in various cultural contexts. The findings highlight the significant advantages of digital technologies in ICH preservation, including their ability to create detailed records, enhance accessibility, and facilitate global dissemination. Specific examples include the use of VR in creating immersive experiences of cultural practices, and 3D scanning for preserving the intricacies of traditional crafts. These technologies not only ensure the preservation of ICH but also contribute to its dynamic transmission across generations and geographies. The study concludes that integrating digital technologies into ICH preservation strategies is not just beneficial but essential for the sustainability of cultural heritage in the digital age. The implications of this research extend to policymakers, cultural institutions, and technologists, emphasizing the need for collaborative efforts in developing and implementing digital preservation strategies that respect and enhance the value of ICH.
Keywords: Digital Technology; Protection; Inheritance; Intangible Cultural Heritage(ICH)